Cytological analysis of bronchoalveolar lavage fluid in asbestos-exposed workers: BALF features in asbestos exposed workers - Sartorelli, Pietro; Indini, Sveva; Bianchi, Francesco; d'Alessandro, Miriana; Bergantini, Laura; Cameli, Paolo; Mazzei, Maria Antonietta; Scancarello, Giuseppina; Barabesi, Lucio; Bargagli, Elena (La Medicina del Lavoro, 2020)
Background: Asbestos-related lung diseases are a group of heterogeneous disorders with different pathogenesis and prognosis. Very few studies investigated the BALF cell profile of asbestos exposed workers. The existence of a relationship between bronchoalveolar lavage fluid (BALF) cellular pattern and specific diagnosis and/or asbestos exposure biomarkers would allow the identification of effect biomarkers useful in the follow up of asbestos-exposed workers and in the diagnosis of asbestos-related diseases. Objectives: To assess BALF cell profile in formerly asbestos-exposed workers and its relationship with asbestos fibre (amphibole and chrysotile) and asbestos body (AB) concentrations. Methods: 113 male workers formerly exposed to asbestos underwent bronchoscopy with bronchoalveolar lavage and were retrospectively enrolled. 35 of them were affected by pleural plaques and 10 were affected by asbestosis. Pulmonary functional tests (PFT), BALF cellular pattern, BALF mineralogical analysis with asbestos fibres and AB counting were performed in each patient. A statistical analysis with a multivariate linear regression model was adopted. Results: From the statistical analysis of data a direct correlation between pack-years and BALF macrophages was found. Inversely correlation between pack-years and BALF lymphocytes was detected. There was not relationship among BALF cellular pattern, PFT values, specific diagnosis, BALF AB count or BALF asbestos fibre concentration. Discussion: BALF cellular pattern does not seem to be related to asbestos exposure biomarkers like AB and asbestos fibre concentration in BALF. Instead, smoke habit can induce an increase in BALF macrophages and a decrease of BALF lymphocytes count.